(untitled) (GEOmedia, 2008)
GOCE brings ’Made in Europe’ to Space Surveyor’s dream of an instrument capable of accurately measuring the Earth’s gravimetry. Such a tool has been realised through the GOCE (Gravity field and steady-state Ocean Circulation Explorer). The ESA satellite ready to launch from Plesetsk russian cosmodrome was also realised. The launch already suffered a couple of delays due to problems with the launcher. ESA will be ready by the next available window to put the satellite in orbit which is the 27th of October.